Use of penile plethysmography in the court: A review of practices in Canada, the United Kingdom and the United States. (18th March 2020) - Murphy, Lisa; Gottfried, Emily; DiMario, Keana; Perkins, Derek; Fedoroff, J. Paul
Abstract : Penile plethysmography (PPG) is an objective measure of male sexual arousal in response to the presentation of a series of erotic and neutral stimuli. This measure is now widely recognized as the most reliable means of objectively measuring male sexual arousal to specific stimuli. Many clinicians and researchers consider PPG to be a vital contribution to the assessment and treatment of adult men with paraphilic interests and men who have committed sex crimes. PPG contributes to the clinical assessment of paraphilic interests, appraisal of risk of recidivism, and provides an objective measurement of changes in sexual arousal in response to treatment. There is strong support for the utility of PPG within clinical and legal contexts. This article addresses ways in which PPG has been utilized in the courts as part of expert clinical opinion. History of its use, details regarding admissibility in court, and case law are explored within the legal systems of Canada, the UK and the USA. Support for the inclusion of PPG as expert evidence is provided and judicial misunderstandings on the rationale for PPG use and its clinical utility in forensic assessments are discussed.